Preparation method of graphene reinforced aluminum-based composite material with mussel-imitated nacreous layer structure
By using "P-B-M" ball milling method and cold pressing processes in aluminum-based composites, graphene-reinforced aluminum-based composites with mussel nacre structure was prepared, which solved the problem of difficult uniform dispersion of graphene in aluminum-based composites and poor interfacial wettability, and significantly improved the mechanical properties and comprehensive properties of the material.
Patent Information
- Application Number
- CN202510268082.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-05-27
AI Technical Summary
Graphene is difficult to disperse evenly in aluminum-based composite materials, and prone to agglomeration, resulting in a decrease in the mechanical properties of the material. The interface wettability between graphene and aluminum matrix is poor, affecting the overall performance of the material.
The ball milling was carried out using the "P-B-M" method, combined with the order of dry milling, wet milling and dry milling, and through the tablet press and cold isostatic pressing, graphene-reinforced aluminum-based composite material with mussel nacre structure was prepared.
The uniform dispersion of graphene in the composite material is achieved, agglomeration is avoided, the mechanical properties and interface bonding strength of the material are improved, and the comprehensive performance of aluminum-based composite material is significantly improved.
Smart Images

Figure CN120041698A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal matrix composites, and particularly relates to a graphene-reinforced aluminum matrix composite with a mussel nacre-like structure. Background Art
[0002] Aluminum and its alloys have become an important part of aerospace materials due to their many excellent properties such as low density, good electrical and thermal conductivity, high specific strength, light weight, corrosion resistance, and good thermal and electrical conductivity. They are widely used in important components such as aircraft antennas, skins, and supports. With the continuous improvement of the comprehensive performance requirements of aluminum materials for strength, modulus, high temperature, wear resistance, and corrosion resistance under modern service conditions, traditional aluminum alloy materials are difficult to meet higher performance requirements. Aluminum matrix composites with aluminum and its alloys as the matrix not only inherit the advantages of a wide range of aluminum alloy selections, easy processing and preparation, and good heat treatment performance, but also have good comprehensive mechanical, physical, and chemical properties. The emergence of high-performance lightweight and high-strength aluminum matrix composites provides a new way to meet the application requirements in the aerospace field, gradually replacing traditional aluminum and other types of composites, and is an indispensable part of aerospace materials.
[0003] Graphene has been considered as one of the ideal reinforcements for improving the comprehensive properties of metal matrix composites due to its low density (1.05 g / cm 3 ), high Young's modulus (1.06 TPa), high specific surface area (2600 m 2 / g), high tensile strength (130 GPa), and high thermal conductivity (5300 W / m·K). By utilizing the excellent electrical, thermal, and mechanical properties of graphene, graphene-reinforced metal matrix composites with excellent properties can be developed. At present, many researchers have conducted certain explorations in the field of graphene-reinforced aluminum matrix composites and achieved a series of results. However, graphene has a very large surface area, which can bring good load transfer effects to the composites. However, due to this, it is very difficult to disperse uniformly in the matrix, especially when the addition amount is relatively high, it is extremely easy to agglomerate, resulting in more material defects and a sharp decrease in mechanical properties. Secondly, due to the poor wettability between graphene and the aluminum matrix, the formed bonding interface is weak. In the powder sintering and forming stage, when the temperature is relatively high, an interfacial reaction occurs between graphite and the aluminum matrix, resulting in the formation of a brittle phase A1 4 C 3, destroying the mechanical properties of the composite material, etc. For the ball milling process of graphene aluminum-based composite materials, during the dry milling process, the charge will be transferred during the ball milling process, and the transferred electrons will fall on the aluminum surface. These charged ions will adsorb the graphene to the aluminum surface, thereby improving the wettability of the graphene and Al interface. The composite powder obtained in the wet milling process reduces the destruction of the graphene structure, and compared with the ball milling dry mixing, the composite powder obtained by ball milling wet mixing has better dispersibility, which is more conducive to the preparation of graphene aluminum-based composite materials with excellent performance, and the graphene can be embedded in the aluminum powder through wet milling.
[0004] As a common biological material in nature, mussels have attracted the attention of many researchers with their unique structure and properties. As the innermost structure of the shell, the nacre has become the focus of research with its orderly "brick wall" structure and extraordinary toughness. The nacre is composed of aragonite crystals and organic matrix arranged in an interlaced manner. This special structure gives the shell strong mechanical properties. The nacre-like structure has excellent properties such as high strength and high toughness, as well as impact resistance. It can be applied to biomedicine, aerospace, tanks, warships and other protective and load-bearing structures, and has broad application prospects. At the same time, in the preparation process of nacre-like composite materials, due to the limitations of the preparation process, equipment, and other environmental factors, different microstructures have different geometric parameters during the preparation of the specimens, and the interface strength also limits the mechanical properties of the bionic composite materials. Summary of the invention
[0005] In view of the material properties and existing problems described in the background technology, the present invention provides a method for preparing a graphene reinforced aluminum-based composite material with a mussel nacreous layer structure, and ball milling is performed using a "PBM" method according to the characteristics of dry grinding, wet grinding, easy agglomeration and uneven dispersion of graphene, and easy cold welding of aluminum powder. Due to the unique characteristics of the nacreous layer structure, the mechanical properties of the composite material are significantly improved compared with pure aluminum. The preparation method of the present invention has a short process time, low cost, and has the potential for industrial production.
[0006] The present invention provides the following steps:
[0007] S1: Mix graphene and aluminum powder and ball mill them according to the "PBM" method to obtain composite powder;
[0008] S2: Dry the wet-milled and dry-milled powders in a vacuum drying oven;
[0009] S3: cold-pressing the dried composite powder using a tablet press to form a block;
[0010] S4: cold isostatic pressing the block to obtain a mussel-like structure composite material;
[0011] S5: sintering the cold isostatically pressed block;
[0012] Furthermore, the addition amount of the graphene is 0.25 wt% - 3 wt% of the total mass of the pure aluminum powder raw material. In the step S1, the ball milling method is "PBM", and "PBM" adopts the sequence of dry milling - wet milling - dry milling. The rotation speeds used for "dry milling - wet milling - dry milling" are 200 rpm - 300 rpm, 200 rpm - 350 rpm and 200 rpm - 400 rpm respectively; the ball - to - powder ratios are 5:1 - 8:1, 8:1 - 10:1, and 10:1 - 20:1 respectively.
[0013] Furthermore, in the "P - B - M" process of step S1, the stages of adding graphene are the first dry milling and wet milling. The addition amount of graphene is 0.25 wt% - 3 wt% of the total mass of the pure aluminum powder raw material. Assuming the total amount of added graphene is (x) g, the amount of graphene added in the first dry milling is (a) g, and the graphene added in the wet milling is a graphene - ethanol solution, with the added amount of graphene being (b) g. The relationship between them is x = a + b (a ≤ x, b ≤ x); before the wet milling stage, a graphene - ethanol solution needs to be added, and the ultrasonic time is 10 min - 30 min.
[0014] Furthermore, the mass ratio of the ultrasonicated graphene - ethanol solution to the ball - milled powder is 3:1 - 5:1.
[0015] Furthermore, the process control agent used in dry milling is stearic acid (analytical pure), and the addition amount is 1% - 3% of the total mass of the powder.
[0016] Furthermore, a protective gas argon is introduced during all ball milling processes.
[0017] Preferably, in step S2, the drying stages are after wet milling and after the final dry milling. The drying temperature is 45°C - 60°C, and the drying time is 4 h - 6 h.
[0018] Furthermore, after drying for 2 h, the vacuum drying oven needs to be opened to release the volatile ethanol gas, and after release, it is evacuated and dried continuously.
[0019] Preferably, in step S3, the cold pressing pressure is 10 MPa - 30 MPa, and the pressure - holding time is 10 s - 60 s.
[0020] Before S4, the block needs to be subjected to a jacket vacuum treatment.
[0021] Furthermore, in step S4, the cold isostatic pressing pressure is 100 MPa - 200 MPa, and the pressure - holding time is 5 min - 30 min.
[0022] Further, in S5, the sintering atmosphere is argon, the sintering temperature is 560°C to 700°C, multi-stage heating and heat preservation are adopted, the starting temperature is room temperature, the heating rate range in the first stage is 4°C / min to 10°C / min, the temperature that can be reached by heating is 350°C to 400°C, the heat preservation time range is 10 min to 30 min, the heating rate range in the second stage is 4°C / min to 10°C / min, the temperature that can be reached by heating is 400°C to 700°C, the heat preservation time range is 1 h to 6 h; the cooling can adopt multi-stage cooling or furnace cooling, the cooling rate range in the first stage is 4°C / min to 7°C / min, the temperature that can be reached by cooling is 350°C to 500°C, and the cooling rate range in the second stage is 2°C / min to 6°C / min or furnace cooling to room temperature. Further, during the ball milling process in step S1, bulk flake aluminum powder is formed, and the particle size of the flake aluminum powder is 20 μm to 70 μm, and the thickness is 1 μm to 3 μm;
[0023] Further, the number of layers of the graphene is 5 to 10 layers, the particle size (D50) of the aluminum powder used is 15 μm to 30 μm, high-energy ball milling is selected for ball milling, the ball milling method is intermittent ball milling (ball milling for 20 min and stopping for 15 min), the ball milling tank used is a stainless steel vacuum ball milling tank, the grinding balls are stainless steel balls, and an inert gas Ar gas needs to be introduced during the ball milling process as a protective gas.
[0024] Compared with the prior art, the beneficial effects of the present invention are:
[0025] The present invention improves on the traditional ball milling method. The graphene in the flake composite powder obtained only by ball milling in the flake aluminum powder obtained by the "PBM" method is evenly distributed. At the same time, "PBM" can ensure the surface roughness, wettability, and integrity of the powder to a certain extent, and can also avoid the agglomeration of graphene to a certain extent. Adding wet milling can also reduce the damage of graphene during the ball milling process. It should be noted that due to the cold welding characteristics of aluminum powder, dry milling must be carried out finally, and the particle size and thickness of the flake aluminum powder are small, so that it can be used as nacre and can fully reflect the structural characteristics.
[0026] In this experiment, a cold pressing - cold isostatic pressing - sintering process was adopted to prepare a graphene - reinforced aluminum matrix composite with a mussel nacre structure. During the sintering process, due to the increased contact surface area of the powders inside the block and the enhanced surface diffusion and grain boundary diffusion activities, an excessively fast sintering rate would lead to thermal stress cracking or deformation. During the ball - milling process and the cold - pressing process, an alumina film would inevitably be generated. When the sintering rate was too slow, its oxide layer could not be removed. At the same time, due to the introduction of graphene, while processing near the melting point of aluminum, it was necessary to ensure a good positive aluminum - carbon interface. Therefore, a multi - stage heat preservation and heating was adopted during the sintering process. Essentially, through the fine regulation of the thermodynamic and kinetic processes, during the low - temperature heat - preservation process at the initial stage of sintering, the organic binder in the powders would decompose and volatilize. After the low - temperature heat - preservation, when heating to a higher temperature, the pore shrinkage and densification were accelerated, and thus a composite material with better performance was obtained.
[0027] Compared with the preparation processes of graphene - reinforced aluminum matrix composites such as vacuum hot - pressing, hot forging - hot rolling, and pressure infiltration method, the production process of this technology has the advantages of short process flow, high economic efficiency, simple operation, and good mechanical properties, and has broad prospects for the large - scale production of graphene aluminum matrix composites. Brief Description of the Drawings
[0028] Figure 1 is the process flow chart of the preparation process of the present invention;
[0029] Figure 2 is the flaky composite powder and cross - section obtained after ball - milling in Example 1 of the present invention;
[0030] Figure 3 is the metallographic diagram of Example 3 of the present invention;
[0031] Figure 4 is the (a) scanning electron microscope image of mussel nacre and (b) scanning electron microscope image of Example 3;
[0032] Figure 5 is the metallographic diagram of Example 7 of the present invention;
[0033] Figure 6 is the hardness distribution diagram of Examples 1 - 7 of the present invention. Detailed Description of the Invention
[0034] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several deformations and improvements can still be made. These all fall within the protection scope of the present invention. The present invention provides a method for preparing a graphene - reinforced aluminum matrix composite with a mussel nacre - like structure.
[0035] Unless otherwise specified, the raw materials used in the present invention can be purchased through commercial channels or prepared by conventional methods. In the following examples, the graphene powder is multi-layer graphene prepared by Nangong Hangzhuo Metal Products Co., Ltd., with the number of layers being 5 - 10 layers. The aluminum powder is from Henan Yuanyang Powder Technology Co., Ltd., with a particle size of 10 - 15 microns, aluminum content ≥ 99.90%. The process control agent is stearic acid (analytical pure). The wet milling medium is graphene - ethanol solution after ultrasonic treatment. All ball milling in this experiment adopts intermittent ball milling, stopping for 15 minutes after ball milling for 20 minutes. During the ball milling process, inert gas Ar is required to be introduced as the protective gas, and the protective gas during the sintering process is argon. Unless otherwise specified, the default room temperature in all examples is 25°C.
[0036] Example 1:
[0037] Take 80 g of aluminum powder and 0.2 g of graphene, dry mill for 3 h. The added process control agent is stearic acid (analytical pure), with a mass accounting for 1 wt% of the total mass of the powder. The graphene content added during dry milling is 0.25 wt%, the rotation speed is 200 rpm, and the ball - to - material ratio is 5:1. Then prepare a graphene - ethanol mixed solution and perform wet milling with the above - dry - milled powder. The graphene content is 0.25 wt%, and the mass ratio of the graphene - ethanol mixed solution to the powder is 1:3. The wet milling time is 6 h, the rotation speed is 300 rpm, and the ball - to - material ratio is 8:1. Every 3 h of ball milling, it is necessary to open the tank to check whether there is a state that is not conducive to ball milling dispersion such as solidification or agglomeration in the tank. If it appears, add an appropriate amount of ethanol solution. Put the wet - milled powder into a vacuum drying oven for drying. The drying time is 4 h, and the drying temperature is 50°C. Dry - mill the dried powder again, add 0.5 wt% of stearic acid, the ball milling time is 4 h, the rotation speed is 350 rpm, and the ball - to - material ratio is 15:1. Dry - mill the ball - milled powder again. The drying time is 2 h to obtain flaky composite powder. Weigh 2.0 g of the composite powder and put it into a stainless - steel mold with a diameter of 15 mm. Use a tablet press to cold - press the dried composite powder into a block. The cold - pressing pressure is 20 MPa, and the pressure - holding time is 20 s. Perform a bag - covering vacuum treatment on the block and put it into a cold isostatic press for isostatic pressing. The cold isostatic pressing pressure is 200 MPa; the pressure - holding time is 5 min. Heat the obtained block from room temperature to 580°C at a rate of 7°C / min, keep it warm for 3 h, and then cool it to room temperature at a rate of 7°C / min. The average hardness of the obtained block is 27.4 HV.
[0038] Example 2:
[0039] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at 7 °C / min, then heated to 580 °C at 4 °C / min, held for 3 h, and cooled to room temperature at 6 °C / min. The average hardness of the obtained block was 40.6 HV.
[0040] Example 3:
[0041] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at 6 °C / min, held for 20 min, then continuously heated to 580 °C at 4 °C / min, held for 3 h, cooled to 350 °C at 5 °C / min, and then furnace-cooled to room temperature. The average hardness of the block was 41.4 HV. By grinding and polishing, a metallographic diagram ( Figure 3 ) can be obtained. By referring to the scanning electron microscope of nacre Figure 4 a, it can be seen that it has the characteristic "brick wall" structure of nacre, showing layer-by-layer stacking, graphene is distributed at the junction, and at the same time, some graphene microflakes are embedded in it.
[0042] Example 4:
[0043] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at 6 °C / min, held for 20 min, then continuously heated to 600 °C at 4 °C / min, held for 3 h, cooled to 350 °C at 5 °C / min, and then furnace-cooled to room temperature. The average hardness of the block was 53.5 HV.
[0044] Example 5:
[0045] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at 6 °C / min, held for 20 min, then continuously heated to 620 °C at 4 °C / min, held for 3 h, cooled to 350 °C at 5 °C / min, and then furnace-cooled to room temperature. The average hardness of the block was 55.8 HV.
[0046] Example 6:
[0047] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at 6 °C / min, held for 20 min, then continuously heated to 640 °C at 4 °C / min, held for 3 h, cooled to 350 °C at 5 °C / min, and then furnace-cooled to room temperature. The average hardness of the block was 60.6 HV.
[0048] Example 7:
[0049] The block prepared by the above method according to Example 1 was heated from room temperature to 350 °C at a rate of 6 °C / min, held for 20 min, then heated to 660 °C at a rate of 4 °C / min, held for 3 h, cooled to 350 °C at a rate of 5 °C / min, and then furnace-cooled to room temperature. The average hardness of the block was 65.5 HV. By grinding and polishing, the metallographic phase can be obtained as Figure 5 shown. It can be inferred that at the grain boundaries, graphene is evenly distributed at the grain boundary intersections, and the structural characteristics are obvious.
[0050] Comparative Example 1:
[0051] As a comparison with Example 3, 2.0 g of pure aluminum powder was taken and placed in a stainless steel mold with a diameter of 15 mm. The dried aluminum powder was cold-pressed using a tablet press to form a block. The cold-pressing pressure was 10 MPa, and the pressure holding time was 20 s. The block was subjected to a vacuum treatment in a sheath, and then placed in a cold isostatic press for isostatic pressing. The cold isostatic pressing pressure was 200 MPa, and the pressure holding time was 5 min. It was heated from room temperature to 350 °C at a rate of 6 °C / min, held for 20 min, then heated to 580 °C at a rate of 4 °C / min, held for 3 h, cooled to 350 °C at a rate of 5 °C, and then furnace-cooled to room temperature. The average hardness of the block was 30.8 HV. Table 1
[0052] From the above examples and comparative examples, it can be seen that with the increase in temperature and the adjustment of the heating and cooling rates, the hardness of the material gradually increases. It can be seen that by finding a suitable sintering process curve, the mechanical properties of the material can be greatly improved. By comparing Table 1, under the same conditions of Example 3 and Comparative Example 1, the hardness of the composite material increased by 30.1% compared with pure aluminum. After adjusting the sintering temperature and the heating and cooling rates, the hardness of the composite material in Example 7 increased by 58.2% compared with Example 3, and increased by 106.7% compared with Comparative Example 1;
[0053] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various deformations or modifications within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a graphene-reinforced aluminum-based composite material having a mussel-like pearl layer structure, characterized in that: The method comprises the following steps: S1: Graphene and aluminum powder are mixed, and the composite powder is obtained by ball milling in the order of "dry grinding-wet grinding-dry grinding" according to the "PBM" method; S2: placing the composite powder after wet grinding and final dry grinding into a vacuum drying oven for drying; S3: cold-pressing the dried composite powder using a tablet press to form a prefabricated block; S4: cold isostatic pressing the prefabricated block; S5: Sintering the cold isostatically pressed block to obtain a mussel nacre-like graphene-reinforced aluminum-based composite material.
2. The preparation method according to claim 1, characterized in that: In the step S1, the amount of graphene added is 0.25wt% to 3wt% of the aluminum powder, the process control agent for dry grinding is stearic acid, and the medium for wet grinding is graphene-ethanol solution; the rotation speeds used for "dry grinding-wet grinding-dry grinding" are 200rpm to 300rpm, 200rpm to 350rpm and 200rpm to 400rpm respectively; the ball-to-material ratios are 5:1 to 8:1, 8:1 to 10:1, and 10:1 to 20:1 respectively.
3. The preparation method according to claim 1, wherein the stages of adding graphene to "PBM" in step S1 are the first dry grinding and wet grinding, assuming that the total amount of graphene added is (x) g, the amount of graphene added in the first dry grinding is (a) g, and the graphene added in the wet grinding is a graphene-ethanol solution, and the amount of graphene added is (b) g, and the relationship between them is x=a+b (a≤x, b≤x); the graphene-ethanol solution needs to be added before the wet grinding stage, and the ultrasonic time is 10min to 30min.
4. The preparation method according to claim 1, characterized in that: The stages that require drying in step S2 are after wet grinding and after final dry grinding in "dry grinding-wet grinding-dry grinding", the drying temperature is 45° C. to 60° C., the drying time after wet grinding is 4 h to 8 h, and the drying time after final dry grinding is 2 h to 4 h.
5. The preparation method according to claim 1, characterized in that: In the step S3, the powder is cold pressed by a mold, the quality of the cold pressed composite powder is determined according to the size of the mold, the cold pressing pressure is 10 MPa to 30 MPa, and the holding time is 10 s to 60 s.
6. The preparation method according to claim 1, characterized in that: In the step S4, the cold isostatic pressing pressure is 100 MPa to 200 MPa, and the holding time is 5 min to 30 min.
7. The preparation method according to claim 1, characterized in that: In the step S5, the sintering atmosphere is argon, the sintering temperature range is 25°C to 700°C, and multi-stage heating and insulation are adopted. The heating rate range of the first stage is 4°C / min to 10°C / min, the temperature can be raised to a range of 350°C to 400°C, and the insulation time range is 10min to 30min. The heating rate range of the second stage is 4°C / min to 10°C / min, the temperature can be raised to a range of 400°C to 700°C, and the insulation time range is 1h to 6h. The cooling can be carried out by multi-stage cooling or furnace cooling. The cooling rate range of the first stage is 4°C / min to 7°C / min, the temperature can be lowered to a range of 350°C to 500°C, and the cooling rate range of the second stage is 2°C / min to 6°C / min or furnace cooling to room temperature.
8. According to the preparation method according to claim 1, during the ball milling process in step S1, flaky aluminum powder is formed, and the particle size of the flaky aluminum powder is 20 μm to 70 μm, and the thickness is 1 μm to 3 μm.
9. The preparation method according to claim 1, characterized in that: The number of layers of the graphene is 5 to 10, the particle size (D50) of the aluminum powder used is 15 μm to 30 μm, a high-energy ball mill is used for ball milling, the ball milling method is intermittent ball milling (ball milling for 20 minutes and stopping for 15 minutes), the ball milling jar used is a stainless steel vacuum ball milling jar, the grinding balls are stainless steel balls, and inert gas Ar gas needs to be introduced as a protective gas during the ball milling process.
10. A graphene-reinforced aluminum-based composite material having a mussel nacre structure prepared according to the method of any one of claims 1 to 9.